Microcatheter contrast injections during intra-arterial thrombolysis increase intracranial hemorrhage risk. (21st April 2010) - Khatri, Rakesh; Khatri, Pooja; Khoury, Jane; Broderick, Joseph; Carrozzella, Janice; Tomsick, Thomas
Abstract : Background and purpose: Combined analysis of the Interventional Management of Stroke I and II trials demonstrated a significant association between microcatheter contrast injections and both intracranial hemorrhage (ICH) and contrast extravasation following combined intravenous (IV) and intra-arterial (IA) thrombolysis. The reliability of these observations was tested in our local registry of IA cases. Design/methods: Treatment angiograms and post-procedure CTs of patients treated with combined IV/IA or IA only recombinant tissue plasminogen activator for ICA-T, M1 or M2 occlusions (n=77) were reviewed. The number of microcatheter injections (MCIs) within/distal to the target occlusion was assigned for every case. The association of MCIs to total ICH, total parenchymal hematoma (PH1+PH2) and PH2 after adjusting for significant covariates was tested. Results: MCIs were used in 21 (27%) cases (range MCI 0–6). Any ICH occurred in 38 (49%) cases, including eight (10%) PH1s and eight (10%) PH2s. The use of MCIs was associated with increased PH (p=0.04), PH2 (p=0.07) and total ICH (p=0.03). MCIs were associated with increased contrast extravasation (CEx) (p=0.02). ICH was observed in all CEx cases (n=5, 100% vs 46% non-CEx; p=0.03), and four (80%) CEx cases developed PH2s (p<0.01). MCIs remained associated with total ICH after adjustment for significant covariates of Thromolysis in Cerebral Infarction score, glucose level and presence of atrial fibrillation (OR 3.60; 95% CI 1.12 to 11.49, p=0.03). MCI use was the only significantly associated covariate for total PHs. Conclusions: MCI use was associated with ICH and with clinically significant PHs in this cohort, providing further evidence that MCIs be reduced during IA thrombolysis.